Hebrews - Moo, Douglas J. (Grand Rapids : Zondervan Academic, 2024)
"The Zondervan Exegetical Commentary on the New Testament series is the go-to resource for pastors and Bible teachers looking for deep but accessible study that equips them to connect the needs of Christians today with the biblical text"--
Includes bibliographical references and index.
Keywords: Bible. -- Commentaries; Commentaries